Evolución de la asignación presupuestaria y su relación con la ejecución del gasto en el ministerio público periodo 2018–2022 - Quispe Veintemilla, Hector Fernando (2025)
The allocation of financial resources to the Public Prosecutor's Office is of paramount importance as it ensures its independence and autonomy in the pursuit of justice, as well as its capacity to conduct efficient investigations, prosecute crimes, combat corruption, and protect individuals' rights. Therefore, the primary objective of this study is to identify the relationship between budget allocation and expenditure execution in the Public Prosecutor's Office during the period 2018-2022. This study, characterized by a correlational level, non experimental design, quantitative approach, and observational nature, identifies a significant and positive relationship between budget allocation and expenditure execution, suggesting efficient resource management. The allocation and execution of current expenditures also show a close relationship, reflecting effective execution. However, no significant relationship was found in capital expenditure, suggesting inconsistency in its management. The variations in budget allocation are perfectly correlated with the execution by the source of financing, demonstrating high efficiency. A constant increase in allocations and expenditure execution was observed, with a 36.7% increase in current expenditure, 35.1% in capital expenditure, and a 109.6% increase in total expenditure execution. Personnel expenditure, although predominant, has decreased, while expenditure on goods and services and non-financial asset acquisitions has increased, indicating a strategy of reallocating resources towards operational investment and infrastructure.